2018
DOI: 10.1007/s13201-018-0695-9
|View full text |Cite
|
Sign up to set email alerts
|

Tritium as tracer of groundwater pollution extension: case study of Andralanitra landfill site, Antananarivo–Madagascar

Abstract: This study aims to understand the extension of groundwater pollution downstream of a landfill, Andralanitra-Antananarivo-Madagascar. Twenty-one samples, composed of dug well waters, spring waters, river, and lake, were measured in stable isotopes (δ 2 H, δ 18 O) and tritium. Results showed that only two dug well waters, collected at the immediate vicinity of the landfill, have high tritium activities (22.82 TU and 10.43 TU), probably of artificial origin. Both upstream and further downstream of the landfill, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Furthermore, elevated tritium contents ranging from 14.9 to 76.6 TU (Table 2) and 10.4 to 22.8 TU (Table 3) were also observed in groundwater that was downgradient to landfills. Conversely, the monitoring of wells that are upstream and also those that are 700 m away downstream from landfills showed depleted tritium contents of 0.84 to 1.46 TU, as evidenced in Table 2 [22]. This is congruent with the study of [21] where the deep groundwater wells 5 and 6, which are farther away from the landfill had very low tritium concentrations (0 to 0.4 TU) throughout the period.…”
Section: Overview Of Isotope Application In Groundwater Studiessupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, elevated tritium contents ranging from 14.9 to 76.6 TU (Table 2) and 10.4 to 22.8 TU (Table 3) were also observed in groundwater that was downgradient to landfills. Conversely, the monitoring of wells that are upstream and also those that are 700 m away downstream from landfills showed depleted tritium contents of 0.84 to 1.46 TU, as evidenced in Table 2 [22]. This is congruent with the study of [21] where the deep groundwater wells 5 and 6, which are farther away from the landfill had very low tritium concentrations (0 to 0.4 TU) throughout the period.…”
Section: Overview Of Isotope Application In Groundwater Studiessupporting
confidence: 77%
“…Since then, the application of environmental isotopes in groundwater and surface water studies has demonstrated their importance in terms of better understanding contaminant flow as well as in pollution source identification. Although several studies have used the isotope ratios of H and O for hydrologic and geochemical investigations, only a few applications [16,21,22], have been reported for dumpsites in developing countries.…”
Section: Overview Of Isotope Application In Groundwater Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the drivers of this increase is landfilling, which contributes to the pollution of drinking water resources (Kjeldsen et al 2002; Lisk 1991). In addition, using landfills as a method of municipal solid waste management has a negative influence on water resources (Ramaroson et al 2018). This form of waste management is still the most commonly used solution in the world (Laner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…or from hospital wastewaters or from biological laboratories as tritium thymidine, which is a tracer used in microbiology laboratories (Tazioli et al, 2002;Tazioli, 2011). Ramaroson et al (2018) shown the extension of groundwater pollution downstream in Madagascar using tritium and stable isotopes (δ 2 H, δ 18 O) analyses. Results showed high tritium activities probably of artificial origin.…”
Section: Discussionmentioning
confidence: 99%